Mouse sperm energy restriction and recovery (SER) revealed novel metabolic pathways - Romarowski, Ana; Fejzo, Jasna; Nayyab, Saman; Martin-Hidalgo, David; Gervasi, Maria G.; Balbach, Melanie; Violante, Sara; Salicioni, Ana M.; Cross, Justin; Levin, Lonny R.; Buck, Jochen; Visconti, Pablo E. (Frontiers in Cell and Developmental Biology, 2023)
Mammalian sperm must undergo capacitation to become fertilization competent. Working in mice, we recently developed a new methodology for treating sperm in vitro that results in higher rates of fertilization and embryo development after in vitro fertilization. Sperm incubated in media devoid of nutrients lose motility although remain viable. Upon re-adding energy substrates, sperm resume motility and become capacitated with improved functionality. Here we explore how this Sperm Energy Restriction and Recovery (SER) treatment affects sperm metabolism and capacitation-associated signaling. Using extracellular flux analysis and metabolite profiling and tracing via Nuclear Magnetic Resonance (NMR) and Mass Spectrometry (MS), we found that levels of many metabolites were altered during the starvation phase of SER. Of particular interest, two metabolites, AMP and L-carnitine, were significantly increased in energy restricted sperm. Upon re-addition of glucose and initiation of capacitation, most metabolite levels recovered, and closely mimic levels observed in capacitating sperm that have not undergone starvation. In both control and SER-treated sperm, incubation in capacitating conditions upregulated glycolysis and oxidative phosphorylation yet ATP levels were diminished presumably reflecting the increased energy consumption during capacitation. Flux data following the fate of 13 C glucose indicate that, similarly to other cells with high glucose consumption rates, pyruvate is converted into 13 Clactate and, with lower efficiency, into 13 C-acetate which are then released to the incubation media. Furthermore, our metabolic flux data show that exogenously supplied glucose is converted into citrate providing evidence that in sperm cells, as in somatic cells, glycolytic products can be converted into Krebs cycle metabolites.